Implementasi Teori Behavioristik Dalam Meningkatkan Kedisiplinan Belajar Peserta Didik Kelas Rendah di Sekolah Dasar - Kartika, Alya Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Study discipline is a crucial element in shaping students' character and academic abilities. The implementation of behaviorist theory serves as an effective strategy to enhance study discipline among lower class elementary school students by focusing on stimulus and response mechanisms. This research aims to evaluate the effectiveness of implementing behaviorist theory in improving study discipline among lower class elementary school students and provide suggestions for a more efficient approach. Literature review methodology is employed to gather and analyze secondary data from relevant sources such as books, journals, and articles. Behaviorist theory emphasizes the role of stimulus and response in shaping student behavior. The application of this theory requires clear feedback, the use of reinforcement or rewards, and the measurement of behavioral changes. Challenges such as reinforcement limitations, measurement issues, adaptation, and the focus on character and creativity development need to be addressed. Implementing behaviorist theory requires appropriate strategies to tackle emerging challenges. Increasing student awareness, using interactive learning methods, and creating a structured learning environment are some suggestions to enhance study discipline among lower class elementary school students using a behaviorist approach.